Issues of time in international, intercultural management: East and Central Europe from the perspective of Austrian managers - Gerhard Fink; Sylvia Meierewert (Journal for East European Management Studies, 2004)
In 339 interviews we identified 449 time related and culturally determined critical incidents. We can clearly distinguish time behaviour of Anglo-German managers from that of managers from France and Italy and East Central Europe. These incidents with East Central European Managers can be grouped in two categories: slow speed of solving tasks and extreme length of negotiations and decision making processes. This time behaviour can be explained by working in collectives and priority setting by supervisors. Risk aversion, harmony seeking, and saving own face are values/culture standards that determine time consuming discussion and decision making behaviour. Wasting time of their (West European) counterparts is of no concern for East Central European Managers, unlike harmony within the collective. – – In 339 Interviews konnten wir 449 zeitbezogene und kulturell determinierte kritische Interaktionssituationen identifizieren. Wir können dabei klar unterscheiden zwischen dem Zeitverhalten englischer/deutscher Manager, dem Verhalten von Managern aus Frankreich und Italien und denen aus Ost- und Mitteleuropa. Diese Situationen mit Managern aus OME können dabei in zwei Kategorien eingeteilt werden: hoher Zeitbedarf bei Problemlösungen und extreme Verzögerungen bei Verhandlungen und Entscheidungsprozessen. Dieses Zeitverhalten kann erklärt werden durch die Arbeitsweise in Kollektiven und die Prioritätensetzung durch den Vorgesetzten. Risikoaversion, Harmoniestreben und Gesichtwahren sind Werte/Kulturstandards die hier zeitaufwändige Diskussionen und Entscheidungsprozeduren beeinflussen. Zeitverschwendung bei ihren (westeuropäischen) Partnern wird von Managern aus OME als nicht so wichtig eingestuft wie die Harmonie im Kollektiv.
Keywords: 650; East Central Europe; Austria; international management